THE EFFECT OF CARTOON VIDEO TO LISTENING COMPREHENSION OF THE STUDENTS OF SMP ISLAM 01 BATU (A Quasy-experimental Research at the 8th Grade Students of Junior High School of SMP Islam Batu) - FARDA AMELIA (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
AbstractThis article aims at examining the effect of cartoon video as listening material to the EFL students’ listening comprehension. Utilizing quantitative approach as the research design, the researcher carried out 30 students of SMP Islam 01 Batu from class 8A and 8B as the participants of the research which were recommended by the teacher. The researcher collected the data by using pretest and posttest mean score which calculated by utilizing SPSS 2.0 to reveal the descriptive of the data, the normality and the homogeneity of the data, and also independent sample t-test. The researcher found that the t-value of the posttest score was more than table (2.884 > 2.048). The null hypothesis (H0) is rejected because the t-test value is more than t-table. The sig (2-tailed) of the data was 0.007 which means that it less than a (0.005) indicated that there is a significant effect of cartoon video to listening comprehension of the 8th grade students of SMP Islam 01 Batu. Based on the finding, using cartoon video as the media to support listening classes might be a good choice with a note that teachers should choose the proper content and also the length of the cartoon video depends on the students’ level of initial listening ability. Key Words: listening comprehension, cartoon video